Older veterans and emergency department discharge information. Issue 10 (3rd May 2012) - Hastings, Susan; Stechuchak, Karen; Oddone, Eugene; Weinberger, Morris; Tucker, Dana; Knaack, William; Schmader, Kenneth
Abstract : Background: Study goals were to assess older veterans' understanding of their emergency department (ED) discharge information and to determine the association between understanding discharge information and patient assessment of overall quality of care. Methods: Telephone interviews were conducted with 305 patients aged 65 or older (or their proxies) within 48 h of discharge from a Veterans Affairs Medical Center ED. Patients were asked about their perceived understanding (at the time of ED discharge) of information about their ED diagnosis, expected course of illness, contingency plan (ie, return precautions, who to call if it got worse, potential medication side effects) and follow-up care. Overall quality of ED care was rated on a four-point scale of poor, fair, good or excellent. Results: Patients or their proxies reported not understanding information about their ED diagnosis (21%), expected course of illness (50%), contingency plan (43%), and how soon they needed to follow-up with their primary care provider (25%). In models adjusted for age and race, a positive association was observed between perceived understanding of the cause of the problem (OR 2.3; 95% CI 1.3 to 4.0), expected duration of symptoms (OR 1.6; 95% CI 1.0 to 2.5) and the contingency plan (OR 2.2; CI 1.3 to 3.4), and rating overall ED care as excellent. Conclusions: Older veterans may not understand key items of information at the time ED discharge, and this may have an impact on how they view the quality of ED care. Strategies are needed to improve communication of ED discharge information to older veterans and their families.